Training on the funding and managing of infak and waqf at the Raudah Al-Jamil foundation, Samarinda - Sigit Hartoko; Nyoria Anggraeni Mersa (Universitas Muhammadiyah Magelang, 2021)
The community service program is in the form of training in the management of infak and waqf at the Al-Jamil Foundation, which is located in the Loa Janan Indah Housing Complex, RT. 01, Farmer Aman Village, Loa anan Ilir District, Samarinda City. The purpose of this community service is to provide understanding of foundation management through the funding and managing of infak and waqf for land purchase and buildings construction of Al-Qur’an Education Center. This community service’s implementation method goes through several stages, namely the stages of planning, preparation, implementation, and evaluation. At the end of the program, the participants have additional knowledge related to strategies for funding, utilizing, and preparing financial reports.